2017
DOI: 10.3390/ijerph14080849
|View full text |Cite
|
Sign up to set email alerts
|

A Multiyear Model of Influenza Vaccination in the United States

Abstract: Vaccinating adults against influenza remains a challenge in the United States. Using data from the Centers for Disease Control and Prevention, we present a model for predicting who receives influenza vaccination in the United States between 2012 and 2014, inclusive. The logistic regression model contains nine predictors: age, pneumococcal vaccination, time since last checkup, highest education level attained, employment, health care coverage, number of personal doctors, smoker status, and annual household inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Factors associated with flu vaccine uptake were largely consistent across racial and ethnic categories, suggesting that some trends in racial/ethnic subgroup vaccine uptake mirror that of the general public – men had lower odds of receiving a vaccination than women, younger individuals had lower odds of receiving a vaccination than older individuals, individuals with a chronic disease received the vaccine more often than those without a chronic disease, and individuals who were not insured had lower uptake of the seasonal flu vaccination ( Kamis et al, 2017 , Lu et al, 2015 , Schmid et al, 2017 , Takayama et al, 2012 , Williams et al, 2017 ). Among NH Whites and NH Blacks, individuals with lower income received vaccinations less often, which may indicate a lack of access healthcare.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Factors associated with flu vaccine uptake were largely consistent across racial and ethnic categories, suggesting that some trends in racial/ethnic subgroup vaccine uptake mirror that of the general public – men had lower odds of receiving a vaccination than women, younger individuals had lower odds of receiving a vaccination than older individuals, individuals with a chronic disease received the vaccine more often than those without a chronic disease, and individuals who were not insured had lower uptake of the seasonal flu vaccination ( Kamis et al, 2017 , Lu et al, 2015 , Schmid et al, 2017 , Takayama et al, 2012 , Williams et al, 2017 ). Among NH Whites and NH Blacks, individuals with lower income received vaccinations less often, which may indicate a lack of access healthcare.…”
Section: Discussionmentioning
confidence: 96%
“…The demographics associated with flu vaccination uptake in the US adult general population are well established – studies have found that race/ethnicity, age, sex, socio-economic-status (SES), insurance, having a usual source of care, contact with physicians, health behaviors, health status, and receipt of other vaccinations, and beliefs are associated with flu vaccine uptake ( Kamis et al, 2017 , Lu et al, 2015 , Schmid et al, 2017 , Takayama et al, 2012 , Williams et al, 2017 ). The majority of literature examining correlates of vaccine uptake compare racial ethnic groups to non-Hispanic (NH) whites ( Budhwani and De, 2016 , Hughes et al, 2019 , Lu et al, 2017 , Lu et al, 2015 , Srivastav et al, 2018 , Stafford et al, 2013 , Tse et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%